PENGARUH FEE AUDIT, PROFESIONALISME PADA KUALITAS AUDIT DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI - Pramesti, I Gusti Ayu Rahma; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
The study aims to analyze the influence of the audit fee and professionalism of auditors on audit quality and job satisfaction as mediation at firms of public accounting in Bali, with auditors on seven offices KAP as many as 81 people as a sample by sample method saturated. The data collection is done by distributing questionnaires and analysis techniques using path analysis. The analysis finds, audit fee and auditor professionalism positive effect on audit quality and job satisfaction is able to mediate the positive effect of the audit fee and professionalism of auditors on audit quality in firms of public accounting in Bali.
Keywords: audit fee, auditor professionalism, job satisfaction and audit quality